The Meaning of Burnout in Nursing Practice: An Interpretative Phenomenological Study among Emergency Department Nurses - Silvana Evi Linda (STIKep PPNI Jawa Barat, 2026)
Background: Burnout is a multidimensional occupational phenomenon that disproportionately affects nurses working in high-intensity environments such as emergency departments (EDs). While quantitative studies have documented its prevalence and determinants, limited research has explored how nurses themselves interpret and make meaning of burnout within their professional and cultural contexts. Objective: This study aimed to explore the lived meaning of burnout among emergency department nurses in Indonesia. Methods: An interpretative phenomenological analysis (IPA) was conducted with ten ED nurses recruited through purposive sampling. Participants self-identified as experiencing burnout and had a minimum of one year of ED experience. Data were collected through in-depth semi-structured interviews and reflective field notes. Analysis followed established IPA procedures, including case-by-case examination, development of emergent themes, and synthesis into superordinate themes. Reflexivity, audit trails, peer debriefing, and member reflection were employed to ensure rigor, in line with COREQ guidelines. Results: Four superordinate themes were identified: (1) burnout as relentless moral and physical overload, (2) burnout as erosion of self and emotional presence, (3) burnout as tension between professional duty and personal life amid limited organizational support, and (4) burnout as a professional test reinterpreted through spirituality and peer solidarity. Burnout was understood not merely as exhaustion, but as a meaning-laden experience involving identity disruption, moral distress, and adaptive resilience. Conclusion: Emergency nurses interpret burnout as a complex lived experience shaped by systemic demands, cultural values, and personal meaning-making processes. Addressing burnout therefore requires organizational reform alongside interventions that acknowledge nurses’ moral, emotional, and spiritual dimensions.